Investigating Students’ Logical Thinking Abilities on Chemistry Learning - Saselah, Yeni Ronalisa (SEAMEO QITEP in Science, 2023)
The purpose of this study is to map students’ logical thinking abilities for learning chemistry. A total of 39 eleventh grade students of SMK-SPP Negeri Samarinda in Agribusiness and Horticulture Program participated in the study. Test of Logical Thinking (TOLT) was administered to determine students’ reasoning abilities. Quantitative descriptive method was used to analyse the data. The result shows that 84,62 % students were found in the concrete level. It consists of 58,97 % male students and 25,64 % female students. Further, 7,69 % male students were found in the transition level and 7,69 % students were found in the formal level, each 2,56 % male and 5,13 % female. From the data, it can be concluded that the majority of students have the concrete level of logical thinking.